South Korea's New Southern Policy: Viewing Indonesia as a Strategic Partner through IK-CEPA - Arifa Rahim; Arfin Sudirman (INDONESIAN GOVERNANCE JOURNAL : KAJIAN POLITIK-PEMERINTAHAN, 2023)
The Indonesia-Korea Comprehensive Economic Partnership Agreement (IK-CEPA) is a significant bilateral agreement in the trade and economic fields between Indonesia and South Korea. It is based on three main pillars: market access for trade in goods and services, trade and investment facilitation, and cooperation and capacity building. This study aims to analyze the bilateral relationship between Indonesia and South Korea through the lens of IK-CEPA, with a particular focus on the rationale, implementation, obstacles, and significance of this cooperation. Using a qualitative approach with a descriptive method, the study collects data through document-based research, internet-based research, and interviews. To ensure data validity and reliability, data triangulation procedures are applied. The study finds that IK-CEPA requires Indonesia and South Korea to commit to higher tariff positions and to facilitate market access and better protection for investors. This fosters a closer relationship between the two countries and enables interdependence. Both countries complement each other's weaknesses to meet their national interests. Although obstacles exist in the negotiation process and the signing of IK-CEPA, the bilateral relationship between Indonesia and South Korea is improving and demonstrating success in economic cooperation.